Regulatory frameworks for reforms of state-owned enterprises in Thailand and Malaysia - Wisuttisak, Pornchai; Abdul Rahman, Nasarudin (Springer, 2021)
State-owned enterprises (SOEs) play a significant role in providing public goods and services such as utilities and infrastructures. They also play a considerable role in promoting a country’s national agenda, such as providing employment opportunities, promoting national corporates and implementing socioeconomic and industrial policy. Since the state is a significant owner of SOEs, the latter enjoy a monopolistic position in the market and have a competitive advantage vis-à-vis other private enterprises. This creates many unintended market consequences such as inefficiency, nontransparency, and weak governance. Various regulatory and institutional frameworks for reforming SOEs have been adopted by countries around the world in order to stimulate competition, increase efficiency, and improve the level of their performance. However, the outcomes of these reforms are rather mixed. In Asia, for example, many SOEs are still operating less efficiently due to their complacent position in the market leading to poor performance. Against this backdrop, this paper aims to explore the experience of regulatory reform of SOEs in Thailand and Malaysia and the challenges that the countries are or have been facing in undertaking such reform. The paper will be divided into five main parts. The second part explores the international perspective of regulatory frameworks, designed to incentivize reforms of SOEs. The third part explores the experience of Thailand and Malaysia in constituting their regulatory frameworks for the reform of SOEs. The fourth part discusses and analyzes the approach of Thailand and Malaysia toward the reform of SOEs as well as issues and challenges associated with such reform. The fifth part concludes the paper and provides some recommendations regarding better regulatory frameworks for the reform of SOEs.